DESIGN OF THE CONTEMPORARY GARMENTS ON THE BASIS OF THE TRANSFORMATION OF STYLISTIC AND ARTISTIC-COMPOSITIONAL CHARACTERISTICS OF TRADITIONAL DECORATIVE ART - Chuprina, N. V.; Remenieva, T. V.; Frolov, I. V.; Tereshchenko, O. H. (Art and Design, 2021)
The purpose. This research aims to analyze artistic-compositional characteristics of Ukrainian traditional embroidery and decorative-applied art (using the example of M. Prymachenko’s art) used in the decoration of the actual ethno-styled garments. Methodology. A systematic approach was used in this research to project authorial contemporary garments: literary-analytical, morphological, and comparative analysis of the creative primary source, associative means of its adaptation to the actual fashion trends. The methodology of the research is based on the systematic analysis of the design projects using elements of the cultural heritage of Ukraine. Systematic-informational and visual-analytical methods were used in this research. Systematic-structural analysis was used to analyze the transformation of artistic-compositional elements in the process of shaping contemporary costumes based on associative transformations. Results. In the process of design project of the authorial collection of female Ethno-style clothes, it was found that decorative art and national garments have a high level of authentic symbolism if used for the actual projection image in conditions of contemporary design activity. Characterizations were given to some principles of implementation of the national image in contemporary trends of fashion industry development. Symbolic image of the floral ornament adapted from Prymachenko’s works as well as stylization of her works in ornamental motifs of the collection were used. Based on pre-project analysis and customer survey it was defined that there is significant interest in national motifs. A collection of female clothes targeted at a wide group of customers was designed. Scientific novelty. Principles of design-project of the collection of contemporary garments with authorial embroidery were proposed using an adaptation of national traditions of female clothes embroidery and folk-art decoration as a basis. Usage of different floral motifs and geometric ornament in ethno-style and implementation of this image as popular among contemporary women in their everyday life were justified. Practical significance lies in the development of principles of formation of authorial costume collection project-image, in justification of principles of ethnographically oriented prints and embroidery and the choice of decoration methods of contemporary female clothes.